Plum Pox virus in japanese plum from Argentina: serological detection and molecular characterization of an isolate from cv. Red Beauty - Dal Zotto, Angelica; Balzarini, Mónica Graciela; Raigon, Juan Manuel; Rossini, Mirta Noemi; Ducasse, Daniel Adrian (Wiley, 2019)
A Plum pox virus (PPV) isolate detected in a Japanese plum orchard in Pocito (San Juan, Argentina) was transmitted mechanically to Prunus tomentosa and Nicotiana benthamiana. DAS-ELISA and DASI-ELISA indicated the virus presence and serological relationship with D-strain isolates; ICRT- PCR amplified a 1.2-kb fragment of the virus genome encoding the CP-3′ nc region. The analysis of the sequence showed the presence of the DAG motif at the 5′ end of the capsid protein and the Rsa I and Alu I sites at the 3′ end. The phylogenetic relationships and multiple alignment with PPV isolates from NCBI database indicated greatest (+98%) homology with the D strain and close identity with MNAT1 (\AF360579) USA peach isolate. The sequence analysed showed two amino acid mutations towards the 5′ N-terminus of CP (the most variable region) with respect to a consensus of PPV D-strain isolates. This is the first molecular characterization of 3′terminal genome region of PPV isolate to confirm D strain in a Japanese plum from Argentina.